Banki spółdzielcze w czasach kryzysu - Kowalczyk, Artur (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
The paper deals with the analysis of the cooperatives bank sector performance in Poland and was surveyed in 30.06.2008–30.06.2009. The research sample covered 60% participation of this sector in Poland and was based on Cooperative Bank Association data. During the research period recorded growing tendency of dynamic development of cooperative banks activity, measured by the level of the balance sum. The profitable relation between deposit and credit value allow to continue financial services, mainly for the credit activity development. The application of conservatism activity in cooperatives bank and strategy of avoiding involvement in risky instruments on capital market, assured high level of security performance